Leukocytosis- A tight roped walk (Indian Journal of Case Reports, 2017)
It is common for patients to reveal a leukocytosis (increased white blood cell count) within twenty four hours of initiation of a glucocorticoid. It is important for clinicians to be aware of this expected side effect and to understand the rationale for such an increase. Here, we present a case of nine years old boy with intracranial space occupying lesion (medulloblastoma) posted for surgery who was on oral steroids and had leucocytosis which gradually subsided on stopping steroids.